ARTFICIAL INTELLIGENCE AND ITS IMPLICATIONS : how smart devices and virtual assistants influence people’s daily lives - Sgarbosa, Pietro; Henrique Del Vechio, Gustavo (Revista Interface Tecnológica, 2020)
Artificial Intelligence is a fascinating area that is present in more and more electronic devices and in the digital universe as a whole, helping human beings in countless tasks, but also shaping and causing certain changes in habits that deserve attention. In this way, this study seeks to assess how intelligent algorithms, such as virtual assistants, digital services, social media, as well as resources available on smart devices, are already naturally integrated into people’s daily lives and are increasingly used not only to solve complex problems, but also to help with everyday trivia. For this, in addition to understanding the theoretical concept of Artificial Intelligence and its implications, the study proposes a survey of 68 young people, whose data allow a more accurate analysis of their view on Artificial Intelligence and how they use it daily. What can be seen from this study is that the use of assistants and intelligent resources gains more and more importance in people’s lives, which demonstrates the trend towards a much more integrated future between men and machines.